Reflexives and Reciprocal relations in Ga (Anaphora) - Otoo, Ruby (Advances in Social Sciences Research Journal, 2016)
In this paper, we examine the devices that the Ga language uses to express anaphoric relations, especially, such notions as one act on one self (reflexive). ‘A acts on B’ and ‘B acts on A’ (reciprocal) and other relationships involving nominal in a particular local domain that results in construing them as having the same referent. This paper, which draws heavily on Carnie (2013, 2002) Haegeman (2006), and Reuland (2001) show that (i) pronouns may function as anaphoric elements in certain syntactic contexts. (ii) reciprocal relations are expressed with verbs and he ‘self/body’ constructions which serve as the reciprocal marker and (iii) reflexives are marked with the use of verbs which indicate that action is being performed on the subject itself or a possessive pronoun plus he (self ) construction.